Utilización de ingredientes innovadores, industriales y comerciales, como alternativas amigables y sostenibles para la alimentación de animales de granja - Macías Mora, Víctor Alexis (2021)
The present research allowed to identify the importance of innovative, industrial and commercial ingredients, as friendly and sustainable alternatives for feeding farm animals. Among them, insect meals are a very promising food source with high nutritional value for animal nutrition. The use of algae in the incorporation of diets improves the health and performance of the animals, due to its nutritional quality. The enzymes allow an excellent use and availability of feed in the feed of farm animals. The mentioned alternatives are involved in reducing costs and improving the productive parameters of farm animals. For the preparation of this document, bibliographic information was collected from books, magazines, graduate theses, newspapers, scientific articles, web pages, congresses, technical manuals and technical bulletins.